An Approach to the Analysis of the Intensity of the International Trade Dynamics on the Example of the European Union Countries - Dziubanovska, N. V.; Maslii, V. V.; Lytvyn, Z. B.; Bliask, V. I. (Statistics of Ukraine, 2022)
International trade is an important component of the national economy of any country in the world, as well as a leading form of international economic relations. Changes in the main indicators of foreign trade, such as exports, imports, trade balance, can cause significant imbalances in the parameters of economic growth of the subjects of such relations.The article proposes an approach to analyzing the intensity of dynamic changes in international trade in goods on the example of EU countries during 2004-2021 with using such methodological approaches as grouping, comparison, calculation and analysis of absolute and relative characteristics of dynamics. For this purpose, two groups of countries where distinguished: countries that were members of the EU before 2004 (Austria, Belgium, Great Britain, Denmark, Ireland, Germany, Spain, Italy, Luxembourg, Netherlands, France, Greece, Portugal, Sweden and Finland) and countries that became members of the EU after 2004 (Latvia, Lithuania, Estonia, Malta, Poland, Slovakia, Slovenia, Czech Republic, Hungary, Cyprus. Bulgaria, Romania and Croatia). In carrying out the study, the cost indicators of trade transactions of the EU countries were used. With the help of such indicators as specific weight, chain and basic growth rates, coefficients of advance, the intensity of export and import dynamics in terms of selected groups where analyzed. The main trends and determinants of the development of export import activities, under the influence of which there were certain changes in the international trade of the EU countries during the period under study, were identified. These determinants include EU enlargement in 2004, the 2009 financial crisis and the COVID 2019 pandemic. Three periods of development of foreign trade of the member countries of this integration group are distinguished. The 5 largest exporter and importer countries, as well as the largest net exporters and net importers in terms of allocated groups, were identified. The results of the analysis also indicate that the countries that joined the EU after 2004 actively used their membership in the context of the development of foreign economic activity: they rapidly increased the volume of merchandise exports and imports. It has been proved that the proposed approach is effective for analyzing the nature of dynamic changes in international trade of any international organizations, integration associations, etc.